2022
DOI: 10.3390/land11091581
|View full text |Cite
|
Sign up to set email alerts
|

Global Research on Contaminated Soil Remediation: A Bibliometric Network Analysis

Abstract: Soil is an important aspect of the ecosystem that plays a crucial role in human population sustainability. Due to natural and anthropogenic activity, soil pollution has become a major environmental issue around the world. Since 1985, researchers have been studying the prevention and treatment of polluted soils. This study used bibliometric approaches to evaluate the soil remediation dataset in the Web of Science database during 2001–2020 to show current research trends and hot themes in quantitative analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Chemical micro-components of pollution are mainly represented by heavy metals, such as cadmium, lead, zinc, copper. These elements are indicators for changes in the ecological state of territories with contaminated soils and territories adjacent to them [14]. Photo from the website of the Ukrainian Nature Protection Group [12] Physical impact involves changing the physical parameters of the soil as a result of the use of weapons and military equipment.…”
Section: Relevance Of the Topic Of Researchmentioning
confidence: 99%
“…Chemical micro-components of pollution are mainly represented by heavy metals, such as cadmium, lead, zinc, copper. These elements are indicators for changes in the ecological state of territories with contaminated soils and territories adjacent to them [14]. Photo from the website of the Ukrainian Nature Protection Group [12] Physical impact involves changing the physical parameters of the soil as a result of the use of weapons and military equipment.…”
Section: Relevance Of the Topic Of Researchmentioning
confidence: 99%
“…Furthermore, the intricate and systemic nature of site remediation necessitates a detailed analysis of how contaminants interact with remediation technologies, which is crucial for refining and enhancing the remediation process [18]. For instance, chemical reduction technology mainly applies to treating non-volatile organic pollutants, with their effectiveness hinging on pollutant properties and environmental conditions [7,19].…”
Section: Introductionmentioning
confidence: 99%
“…Areas where there is, or has been, strong industrial activity have been identified as key indicators for pollution increase and instability of ecosystems. This fact is not only related to the industrial activity they carry out but also to all the transport of raw materials and manufactured goods, like rail and port complexes associated with it, that promotes the formation of oil spill areas [2,26,27].…”
Section: Introductionmentioning
confidence: 99%